Universidade e sociedade: faces da extensão na UFPA - GONÇALVES, Rosilene Ferreira (Universidade Federal do Pará, 2013)
This study on the relation university and society in the view of the Extension of the Federal University of Pará (UFPA), based on the analysis of three dimensions: the institutional policy, the academic formation and valorization and the relation with the society. Through this work, one tries to understand how the Extension of the University in the institution happens, as well as to verify what the contribution of this activity for the performers directly involved in extensionist projects. The research was held in three projects under development at the UFPA: Projeto Riacho Doce (PRD), Rádio-Ação (PRA) and Projeto Atenção Integral em Saúde Bucal na Creche Sorena (PAISB), which are representative in the thematic areas of education, culture and health. During the research it has been adopted the qualitative and quantitative approaches, and as techniques, the participating observation in the projects, interviews and questionnaires with the manager of the extension, professors and students of the UFPA, communities assisted by the projects and a PRD partner. It has been noticed that the Extension of the University at UFPA is under building process of its institutional validity and it has been strengthened in this last decade by the Forum of Pro-Rectors of Extension of Brazilian Universities, considered as the main reference at the boundary of conceptions and forms of organization of the extensionist programs and projects in the institution. It is common to notice, in the researched subjects, a conception of Extension very much based on the traditional patterns, although new elements have been added to it, considering the understanding of this activity as academic and integrating. It has also been observed the manifestation of differentiated patterns of making Extension, which are concrete in several organizational structures, whose main objective is to enlarge its life cycle. Both professors and students are unanimous in pointing out the importance of this activity for their personal, academic and professional life, in spite of the fact that a lot of clogs are pointed out in this process. Eventually the study shows that there are channels of communication of the university with the society, which need to be widened in order to change them into privileged forums of guidance of the extensionist activities. It comes to conclude that it is possible to see the academic and social strengthening of the Extension, even if several factors are necessary for its reach in the education scenery.